Advances in pharmacotherapy for opioid-induced constipation – a systematic review. (March 2015) - Siemens, Waldemar; Gaertner, Jan; Becker, Gerhild
<x xml:space="preserve">Abstract</x> Introduction: Opioid-induced constipation (OIC) is one of the most frequent and burdening adverse events (AE) of opioid therapy. This systematic review aimed to evaluate efficacy and safety of drugs in randomized controlled trials (RCTs) with adult OIC patients. Areas covered: Efficacy assessment focused on objective outcome measures (OOMs): bowel movement (BM) frequency, BM within 4 h and time to first BM. Twenty-one studies examining seven drugs were identified. Methylnaltrexone showed improvements in all three OOMs. RCTs in naloxone and alvimopan tended to be effective for BM frequency measures. Naloxegol (≥ 12.5 mg) improved all OOMs. Though effectiveness of lubiprostone was demonstrated for all OOMs, group differences were small to moderate. CB-5945 and prucalopride tended to increase BM frequency, especially for 0.1 mg twice daily and 4 mg daily, respectively. Besides nausea and diarrhea, abdominal pain was the most frequent AE for all drugs (risk ratio, range: 1.52 – 5.06) except for alvimopan. Treatment-related serious AEs were slightly higher for alvimopan (cardiac events) and prucalopride (severe abdominal pain, headache). Pain scores for placebo and intervention groups were similar for all drugs. Expert opinion: Finding a consensus definition and inclusion criteria for OIC plus a rational balance between efficacy and AEs of drugs remain future challenges.